Dental Therapists in the United States: Health Equity, Advancing. (October 2021) - Mertz, Elizabeth; Kottek, Aubri; Werts, Miranda; Langelier, Margaret; Surdu, Simona; Moore, Jean
Abstract : Background: Dental therapists (DTs) are primary care dental providers, used globally, and were introduced in the United States (US) in 2005. DTs have now been adopted in 13 states and several Tribal nations. Objectives: The objective of this study is to qualitatively examine the drivers and outcomes of the US dental therapy movement through a health equity lens, including community engagement, implementation and dissemination, and access to oral health care. Methods: The study compiled a comprehensive document library on the dental therapy movement including literature, grant documents, media and press, and gray literature. Key stakeholder interviews were conducted across the spectrum of engagement in the movement. Dedoose software was used for qualitative coding. Themes were assessed within a holistic model of oral health equity. Findings: Health equity is a driving force for dental therapy adoption. Community engagement has been evident in diverse statewide coalitions. National accreditation standards for education programs that can be deployed in 3 years without an advanced degree reduces educational barriers for improving workforce diversity. Safe, high-quality care, improvements in access, and patient acceptability have been well documented for DTs in practice. Conclusion: Having firmly taken root politically, the impact of the dental therapy movement in the US, and the long-term health impacts, will depend on the path of implementation and a sustained commitment to the health equity principle. Abstract : Supplemental Digital Content is available in the text.